SMEs as Community Assets: Exploring Management Strategies for Sustainable Development - Setiadi, Wawan (Golden Ratio of Community Services and Dedication, 2023)
This study explores management strategies for sustainable development within Small and Medium-sized Enterprises (SMEs), focusing on their role as community assets. The research aims to elucidate the drivers and mechanisms shaping SMEs' engagement in sustainable practices, with a particular emphasis on flexibility, innovation, local engagement, and the integration of sustainability principles. The methodological approach involves a comprehensive literature review, drawing on theoretical frameworks and empirical studies to analyze the multifaceted nature of SMEs' sustainability practices. Key findings indicate that SMEs exhibit inherent flexibility and innovation, enabling them to navigate market dynamics and technological advancements effectively. Moreover, their emphasis on local engagement fosters social cohesion and cultural preservation, contributing to economic resilience and community well-being. Additionally, the integration of sustainability principles into SMEs' management practices emerges as a significant trend, reflecting a growing recognition of their role in advancing sustainable development goals. The study underscores the importance of collaborative approaches involving policymakers, practitioners, and stakeholders to support and promote sustainable SME development. Overall, the findings highlight the transformative potential of SMEs as drivers of sustainable development at the grassroots level.